Represented Reporters: Images of War Correspondents in Memoirs and Fiction - Korte, Barbara (transcript, 2015)
War correspondents are prominent actors in the media world. They took hold in the cultural imaginary soon after their profession had been created in the mid-19th century. With a particular focus on Britain, this study investigates the representation of war correspondents from Victorian times to the present, in memoirs, novels and films. Such representations react to prevailing notions that exist about war reporters and participate in their further construction. With its cultural approach, this book complements studies of war correspondents in media and communication studies, history and ethnology.